Using QR codes for continuous assessment in higher education - Virginia Jiménez Rodríguez; Carmen Llopis Pablos; Patricia Jara Calaforra Faubel; Pierre Josué Almagro Lapo; Jesús María Alvarado Izquierdo; Aníbal Puente Ferreras (Centro de Estudios Financieros, 2016)
The implementation of information and communications technology (ICT) in education has accelerated in recent years. At university level educational platforms that provide access to the contents of different subjects are used, as well as on-line communication between teachers and students. This project intended to improve teacher quality and motivation and satisfaction in 1st grade students, through the insertion of new ICT tools [forms Google and QR codes (quick response codes)] that allow students the continuous assessment of their own learning, with particular emphasis on the application of metacognitive strategies for problem solving. It was conducted during the academic year 2014-2015 in the subject of Basic Psychology (practices). The subject Basic Psychology is taught in 1st Degree of Social Work at the Complutense University of Madrid. It consists of six ECTS (European Credit Transfer and Accumulation System) credits and as such, students receive two hours of lecture and practical class one hour each week. It was during the weekly hour of practice which was carried out this innovation project.